Transformasi Pendidikan Islam di Pesantren : Mempertahankan Identitas di Era Globalisasi - Bulhayat (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the transformation of Islamic education in Islamic boarding schools (pesantren), highlighting efforts to integrate the preservation of tradition with the application of modernization to face the challenges of globalization. As the oldest Islamic educational institutions in Indonesia, Islamic boarding schools (pesantren) have a strong tradition of scholarship through the teaching of yellow books, the sorogan and bandongan methods, and the practice of daily worship. However, technological developments, curriculum modernization, and global demands require Islamic boarding schools to integrate religious knowledge with general knowledge, 21st-century skills, and the use of digital technology. This study uses a qualitative library research approach with primary sources in the form of classical books, curriculum documents, and government regulations, as well as secondary sources from related academic literature. The data obtained were analyzed through content analysis to identify the main themes of the transformation of Islamic boarding school education. The results of the analysis show that the transformation of Islamic boarding schools includes adaptive curriculum innovation, the implementation of active learning methods, the use of digital technology, and a shift in the leadership style of kiai from a charismatic-traditional model to a participatory and professional pattern. The principle of al-Muḥāfaẓah ‘alā al-Qadīm al-Ṣāliḥ wa al-Akhdu bi al-Jadīd al-Aṣlaḥ is a philosophical foundation that maintains the identity of Islamic boarding schools while enabling the acceptance of beneficial reforms. This transformation not only strengthens the identity of Islamic boarding schools but also ensures their sustainability and competitiveness in the era of globalization. Thus, Islamic boarding schools now serve as inclusive, adaptive, and multifunctional centers of Islamic education, capable of making a real contribution to the development of modern society